PENGEMBANGAN INSTRUMEN TES BERBASIS KETERAMPILAN PROSES SAINS PADA MATERI RANGKA KELAS IV SDN 050 TARAKAN - Anita Markus; Muhsina Annisa; Kartini Kartini (Universitas Borneo Tarakan, 2019)
The type of research used is Research and Development design Formative Evaluation (Tessmer in Rahayu, 2008). The subject ofthe study was class IV. The result of the research is 30 item in the formof multiple choice. The first stage of expert validation is the firstvalidation of the content experts of 80% in effective category, the secondvalidation of the construction expert of 80% in effective category, thethird validation of linguists by 93% in the very effective category. Inone-to-one trials students response of 83% in the effective category.The results of small group trials in the form of student responses by 89%included in the category very effective. Based on the inputs andcomments of small group of test instruments improved and then field testwas conducted on 60 students of grade IV SDN 050 Tarakan. Result ofanalysis by using SPSS 21 program showed 24 item in valid category,reliability value that is r11=0,650 r tabel=0,254 in high category incriterion of reliability. Data analysis using AnatesV4 program showeddifficulty level with easy criteria of 1 items about (3,3%), mediumcriterion 26 items about (86,7%), difficult criterion 3 items about (10%),different with bad 4 item about (3.33%), different power with sufficientcriteria 14 items about (46.67%), different with good criterion 9 itemsabout (30%), different with very good criterion 3 items about (10%),produces effective deception as many as 26 items about (86.7%).